Penerapan Manajemen Strategik Dalam Menghadapi Pandemi Covid 19 - Dian Sudiantini; N.Titi Rahmah; Muhammad Fahriansyah; Muhammad Yossi Alviansyah (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The Covid-19 pandemic has had a significant impact around the world, including in the health, social, economic and political fields. Therefore, implementing strategic management is very important in dealing with this pandemic. Strategic management is the process of planning, organizing, controlling, and making decisions in achieving long-term organizational goals. In the context of the Covid-19 pandemic, strategic management must be directed at efforts to minimize the negative impact of the pandemic, while maximizing the potential benefits that can be gained from this situation. The implementation of strategic management in dealing with the Covid-19 pandemic can be done in several ways, among others, the first is Strengthening the health system: The first step in dealing with the Covid-19 pandemic is to strengthen the existing health system. This includes increasing hospital capacity, increasing the availability of medical equipment, and increasing the number of available medical personnel.